Placing a lumen-apposing metal stent despite ascites: feasibility and safety - Irani, Shayan (VideoGIE, 2020)
BACKGROUND AND AIMS: Placing a lumen-apposing metal stent (LAMS) through ascites carries serious risks, including death from leakage around the LAMS and failure to create a mature fistula between the 2 lumens. However, sometimes no options exist or are equally dangerous. We present 5 patients who underwent LAMS placement despite ascites in 2 different locations. METHODS: This is a retrospective review of 5 patients who underwent LAMS placement despite ascites in 2 different locations from 2016 to 2018. RESULTS: Three patients with cholecystitis and 2 patients with afferent limb syndrome and severe ascites were treated with a combination of preprocedural and intraprocedural paracentesis. Serum ascites albumin gradient was measured. Weight was recorded daily. Patients were encouraged to sleep at an incline, and periodic paracentesis (every 3-7 days) was performed when ascites reaccumulated over 4 weeks. Median volume of ascites aspirated was 2 L preprocedurally and 300 mL intraprocedurally. Only 1 patient had ascites with a high serum ascites albumin gradient and was treated with diuretics. Technical and clinical success was achieved in all 5 patients without any adverse events over a median follow-up of 28 weeks. CONCLUSIONS: In situations in which no better options remain, LAMS placement appears to be safe after adequate and aggressive treatment of the underlying ascites pre-, intra-, and postprocedurally. Larger studies are needed to establish the safety of this approach.